High-affinity T helper epitope induces complementary helper and APC polarization, increased CTL, and protection against viral infection - Ahlers, Jeffrey D. (American Society for Clinical Investigation, 2001)
Natural viral proteins do not always make optimal vaccines. We have found that sequence modification to increase epitope affinity for class II MHC molecules (epitope enhancement) can improve immunogenicity. Here we show first that a higher-affinity helper epitope-enhanced HIV vaccine not only induces more cytotoxic T lymphocytes (CTLs), but also skews helper cells toward Th1 cytokine production and protects against HIV-1 recombinant vaccinia viral challenge. Furthermore, we elucidate a novel mechanism in which the higher-affinity vaccine induces dramatically more effective helper cells with a higher level of CD40L per helper cell and more positive cells, which in turn more effectively conditions dendritic cells (DCs) for CTL activation in a second culture. The improved helper cells also induce much greater IL-12 production by DCs, accounting for the reciprocal T helper polarization to Th1, and increase costimulatory molecule expression. Thus, increasing affinity for class II MHC results in a complementary interaction in which T helper and antigen-presenting cells polarize each other, as well as increase CTL, and provide greater vaccine efficacy against viral infection.